2021
DOI: 10.1186/s12575-021-00148-6
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Microbiota in SARS-CoV-2 Positive and Negative Patients

Abstract: We investigated nasopharyngeal microbial community structure in COVID-19-positive and -negative patients. High-throughput 16S ribosomal RNA gene amplicon sequencing revealed significant microbial community structure differences between COVID-19-positive and -negative patients. This proof-of-concept study demonstrates that: (1) nasopharyngeal microbiome communities can be assessed using collection samples already collected for SARS-CoV-2 testing (viral transport media) and (2) SARS-CoV-2 infection is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
(26 reference statements)
8
28
1
1
Order By: Relevance
“…Propionibacteriaceae, or Corynebacteriam accolens, as was reported for a study of 50 patients (n = 40 positive, 10 negative) in Baltimore [3]. Another study found no differences in the nasopharyngeal microbiota of patients who had mild COVID-19 (n = 9 positive, 10 negative) [2]. Analysis of patient samples in Nashville (n = 38 mild to moderate positive, 21 negative) revealed the complexity of interaction between viruses and bacteria in the upper respiratory tract, as differences in the airway microbiome were reported to be dependent on the SARS-CoV-2 viral load [16].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Propionibacteriaceae, or Corynebacteriam accolens, as was reported for a study of 50 patients (n = 40 positive, 10 negative) in Baltimore [3]. Another study found no differences in the nasopharyngeal microbiota of patients who had mild COVID-19 (n = 9 positive, 10 negative) [2]. Analysis of patient samples in Nashville (n = 38 mild to moderate positive, 21 negative) revealed the complexity of interaction between viruses and bacteria in the upper respiratory tract, as differences in the airway microbiome were reported to be dependent on the SARS-CoV-2 viral load [16].…”
Section: Discussionsupporting
confidence: 63%
“…The samples were nasopharyngeal swabs in viral transport media (VTM) collected under IRB-approved protocol 2019.334 along with metadata in 3-8 April 2020 in Louisiana, USA. The utility of this type of medical waste sample for microbiome studies has been previously established for Influenza [19] and SARS-CoV-2 [2,20]. Demographics associated with the samples are presented in Table 1 and are representative of the demographic breakdown of testing at the time.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Braun et al [37] (n=33), De Maio et al [38] (n=40), and Liu et al [39] (n=9) showed no significant differences in the nasopharyngeal microbial community between COVID-19 and control patients using α-ÎČ diversity and taxonomic compositional analysis. Whereas Mostafa et al [40] (n=50) and Engen et al [41] (n=19) reported a lower α diversity (Chao1, Shannon, and Simpson indexes) in COVID-19 compared to healthy patients, and both groups showed significant dissimilarities in ÎČ diversity. Therefore, there is controversy regarding lung and nasopharyngeal microbiota composition on SARS-CoV2 infection.…”
Section: Discussionmentioning
confidence: 89%